Behind Her Eyes : A suspenseful psychological thriller - Pinborough, Sarah ([S.l.]: Flatiron Books, 2017)
AN INSTANT New York Times Bestseller You should read Behind Her Eyes...It's bloody brilliant. --Stephen King "An eerie thriller...Pinborough keeps us guessing about just who's manipulating whom - until the ending reveals that we've been wholly complicit in this terrifying mind game. --The New York Times Book Review Why is everyone talking about the ending of Sarah Pinborough's Behind Her Eyes? Louise is a single mom, a secretary, stuck in a modern-day rut. On a rare night out, she meets a man in a bar and sparks fly. Though he leaves after they kiss, she's thrilled she ...
General adult.